2011
DOI: 10.1002/hlca.201000156
|View full text |Cite
|
Sign up to set email alerts
|

Seven New Lignan Esters from Kadsura philippinensis

Abstract: Five new oxygenated lignans with a dibenzocyclooctadiene skeleton, kadsuphilols P -T (1 -5), and two new C 19 homolignans, kadsuphilols U and V (6 and 7), were isolated by chromatographic fractionation of an AcOEt extract of the stems of Kadsura philippinensis. The structures of the isolated metabolites were elucidated through extensive spectroscopic analysis including HR-ESI-MS and 2D-NMR (HMQC, COSY, and HMBC). The configuration at the chiral centers and at the biphenyl moiety were determined by interpretati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…A 95% ethanol extract of the dried roots of K. longipedunculata was subjected to a combination of chromatographic steps on silica gel, Sephadex LH-20, and semipreparative HPLC to afford the new longipedlignans A–J ( 1 – 10 ) and 18 known lignans, heteroclitin D ( 11 ), heteroclitin H ( 12 ), schiarisanrin D ( 13 ), schiarisanrin C ( 14 ), schiarisanrin B ( 15 ), kadsulignan I ( 16 ), 9- O -benzoyloxokadsuranol ( 17 ), 9- O -isovaleroyloxo­kadsuranol ( 18 ), 9- O -propanoyloxo­kadsuranol ( 19 ), heteroclitin Ia ( 20 ), heteroclitin E ( 21 ), heteroclitin Ib ( 22 ), binankadsurin A ( 23 ), 7- O -acetylbinankadsurin A ( 24 ), heteroclitin P ( 25 ), kadsuphilol T ( 26 ), kadsuphilol B ( 27 ), and schisandlignan D ( 28 ) (Figure ). The structures of the known compounds were determined by spectroscopic/spectrometric data analysis and comparison to literature values.…”
Section: Results and Discussionmentioning
confidence: 99%
“…A 95% ethanol extract of the dried roots of K. longipedunculata was subjected to a combination of chromatographic steps on silica gel, Sephadex LH-20, and semipreparative HPLC to afford the new longipedlignans A–J ( 1 – 10 ) and 18 known lignans, heteroclitin D ( 11 ), heteroclitin H ( 12 ), schiarisanrin D ( 13 ), schiarisanrin C ( 14 ), schiarisanrin B ( 15 ), kadsulignan I ( 16 ), 9- O -benzoyloxokadsuranol ( 17 ), 9- O -isovaleroyloxo­kadsuranol ( 18 ), 9- O -propanoyloxo­kadsuranol ( 19 ), heteroclitin Ia ( 20 ), heteroclitin E ( 21 ), heteroclitin Ib ( 22 ), binankadsurin A ( 23 ), 7- O -acetylbinankadsurin A ( 24 ), heteroclitin P ( 25 ), kadsuphilol T ( 26 ), kadsuphilol B ( 27 ), and schisandlignan D ( 28 ) (Figure ). The structures of the known compounds were determined by spectroscopic/spectrometric data analysis and comparison to literature values.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The UV, 1D-NMR, and ECD data showed that 5 is an S -biphenyl–configured dibenzocyclooctadiene lignan. Comparison of the spectral data of 9 with kadsuphilol R ( Cheng et al, 2011 ) exhibited the presence of the isobutyryl moiety instead of the angeloyl moiety at C-9 in 5 . The HMBC correlations from H-9 ( δ H 5.70) to C-1'' ( δ C 176.8) and from H-2'' ( δ H 1.93), H-3'' ( δ H 0.88), and H-4'' ( δ H 0.87) to C-1'' ( δ C 176.8) in 5 established the locations of the isobutyryl group at C-9.…”
Section: Resultsmentioning
confidence: 99%
“…Forty-three known compounds isolated during this project were characterized as lancilactone B ( 9 ) ( Chen et al, 1999 ), kadsudilactone ( 10 ) ( Rui et al, 1991 ), schisanlactone B ( 11 ) ( Liu et al, 1983b ), kadsuphilactone B ( 12 ) ( Shen et al, 2005 ), xuetongsu ( 13 ) ( Shehla et al, 2020 ), heteroclitalactone A ( 14 ) ( Wang et al, 2006a ), changnanic acid ( 15 ) ( Liu and Huang, 1991 ), cycloartenone ( 16 ) ( Wang et al, 2006a ), schizandronic acid ( 17 ) ( Li et al, 2003 ), seco -coccinic acid F ( 18 ) ( Minh et al, 2014 ), kadsuracoccinic acid B ( 19 ) ( Li et al, 2008 ), sorghumol ( 20 ) ( Cambie et al, 1992 ), heteroclitalignan D ( 21 ) ( Wang et al, 2006b ), kadsurarin ( 22 ) ( Chen et al, 1973 ), kadsuphilol T ( 23 ) ( Cheng et al, 2011 ), kadsuphilol R ( 24 ) ( Cheng et al, 2011 ), kadsuphilol C ( 25 ) ( Luo et al, 2017 ), kadsulignan N ( 26 ) ( Gao et al, 1998 ), enshizhisu ( 27 ) ( Huang et al, 1982 ), machilolin A ( 28 ) ( Chen et al, 2009 ), (+)-pinoresinol ( 29 ) ( Fan et al, 2020 ), (+)-2-(3,4-dimethoxyphenyl)-6-(3,4-dimethoxyphenyl)-3,7-dioxabicyclo [3,3,0] octane ( 30 ) ( Latip et al, 1999 ), meso -dihydroguaiaretic acid ( 31 ) ( Lu and Chen, 2008 ), 6α,​9α-​dihydroxycadinan-​4-​en-​3-​one ( 32 ) ( Cao et al, 2019c ), (4 R )-4-hydroxy-1,10- seco -muurol-5-ene-1,10-dione ( 33 ) ( Kiem et al, 2014 ), litseachromolaevane A ( 34 ) ( Zhang et al, 2003 ), cryptomeridiol ( 35 ) ( Ragasa et al, 2005 ), (-)-5 β ,11-dihydroxyiphionan-4-one ( 36 ) ( Lin et al, 2019 ), aromadendrane-4 β ,10 α -diol ( 37 ) ( Goldsby and Burke, 1987 ), lochmolin F ( 38 ) ( Tseng et al, 2012 ), loliolide ( 39 ) ( Kim et al, 2004 ), β- sitosterol ( 40 ) ( Luo et al, 2009 ), daucosterol ( 41 ) ( Tezuka et al, 1998 ), stigmasterol ( 42 ) ( Luo et al, 2009 ), schleicheol 2 ( 43 ) ( Pettit et al, 2000 ), 7-hydroxy- β- sito...…”
Section: Resultsmentioning
confidence: 99%
“…is an evergreen vine, mainly distributed at low altitude onremote islands of Taiwan such as Green Island [9]. Our previous phytochemical studies on the EtOAc extracts of K. philippinensis resulted in the isolation of two novel triterpene dilactones and many lignans [10,11,12,13,14,15,16,17]. In this paper, we report the isolation and structure elucidation of three new C19 homolignans, named taiwankadsurins D-F, and two new C18 lignans, designated kadsuphilins N and O.…”
Section: Introductionmentioning
confidence: 99%